2018
DOI: 10.1002/chem.201800535
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Electrochemical Reduction of Dinitrogen to Ammonia at Ambient Temperature and Pressure over Iron Oxide Catalysts

Abstract: The catalytic conversion of dinitrogen (N ) into ammonia under ambient conditions represents one of the Holy Grails in sustainable chemistry. As a potential alternative to the Haber-Bosch process, the electrochemical reduction of N to NH is attractive owing to its renewability and flexibility, as well as its sustainability for producing and storing value-added chemicals from the abundant feedstock of water and nitrogen on earth. However, owing to the kinetically complex and energetically challenging N reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 62 publications
(157 reference statements)
4
85
0
Order By: Relevance
“…To further clarify the difference, the O 1 s spectrum of Ru/TiO 2 -Vo was fitted to three individual peaks representing different oxygen environment. Three different peaks located at around 530.1, 531.4 and 532.3 eV were assigned to the oxygen lattice (O L ), oxygen species in the vicinity of the oxygen vacancy (Vo) and the chemisorbed oxygen species (O C ), respectively [47,48] . Unfortunately, the O 1 s spectra of Ru/TiO 2 was only fitted to two peaks located at around 530.1 and 532.3 eV representing O L and O C , which was similar with the sample of Ru/P25 (Fig.…”
Section: S1amentioning
confidence: 99%
“…To further clarify the difference, the O 1 s spectrum of Ru/TiO 2 -Vo was fitted to three individual peaks representing different oxygen environment. Three different peaks located at around 530.1, 531.4 and 532.3 eV were assigned to the oxygen lattice (O L ), oxygen species in the vicinity of the oxygen vacancy (Vo) and the chemisorbed oxygen species (O C ), respectively [47,48] . Unfortunately, the O 1 s spectra of Ru/TiO 2 was only fitted to two peaks located at around 530.1 and 532.3 eV representing O L and O C , which was similar with the sample of Ru/P25 (Fig.…”
Section: S1amentioning
confidence: 99%
“…The Fe 2 O 3 -CNTs had ag ood electrochemical stability and could be used for at least 60 h. The data also indicated that the electrocatalytic syn-thesis of active sites in NH 3 mayb ea ssociated with specific carbon sites formed att he interface between Fe 2 O 3 and CNTs. Cui et al [118] proved that the a-Fe 2 O 3 /CNT catalyst with abundant oxygen vacancies could improvet he NH 3 yield andF Eo f N 2 reduction under ambient conditions. Electrochemical tests in 0.1 m KOH as the electrolyte as ap otential of À0.9 Vv s. Ag/ AgCl revealed an improved NRR performance.…”
mentioning
confidence: 99%
“…The FEs of α‐Fe 2 O 3 @mTiO 2 ‐400 for NH 3 formation are shown in Figure e. The FEs are 9.9 %, 13.3 %, 9.5 %, 2.1 %, and 1.1 % at −0.4, −0.5, −0.6, −0.7, and −0.8 V, respectively. In addition, it is noteworthy that the FE (13.3 %) at −0.5 V is better than the catalytic activity of that of most reported aqueous‐ and Fe‐ based NRR electrocatalysts under ambient temperature and pressure conditions, including γ‐Fe 2 O 3 ‐NC/CF (12.28 %), Fe/Fe 3 O 4 (8.29 %), Fe 2 O 3 /CNT (0.164 %), Fe 2 O 3 ‐Ar/CNT (8.28 %) . Notably, the competition between the NRR and the HER lead to the yield rate and FE of NH 3 value are decreased with potential being more negative (<‐0.5 V) .…”
Section: Methodsmentioning
confidence: 94%